Proposed interior design scheme of The Backpackers Hostel for BackHome Kuala Lumpur Sdn Bhd at Terminal Bas Ekspres Medan Gopeng, 31650, Ipoh, Perak / Khalilah Mohd Annuar - Mohd Annuar, Khalilah (Faculty of Architecture, Planning and Surveying, 2011)
This final semester we were given a task either to propose new interior design schemeor doing upgrading project. I proposed a new interior design scheme of The Backpackers Hostel for BackHome Kuala Lumpur Sdn. Bhd. as my client. It is a backpackers hostel and categorised under boutique hotel. The client have an intention to open a new branch. I have observe the upper level of Terminal Bas Ekspres Medan Gopeng and found that it was like empty even there were foodcourt, multifunction hall and a few shops and retails. So, I decided to choose it as the proposed site. This project was then followed by a few stages of progress. Firstly is to collect as much information as possible about our client such as client’s background, achievement, organisation, and client’s mission. To do so, I do research by internet, an interview with the client and do some case study. The stages goes by proposal stage followed by planning stage and lastly final presentation. By completing these three stages, the project will declared as complete.